Studi Kelayakan Operasional untuk Pendirian Resort di Kawasan Terpencil - Avira Agamila; Hendro Soejadi; Mochamad Thariq Yafi Soejadi; Budi setiawan; Murhadi Murhadi (Lembaga Pengembangan Kinerja Dosen, 2025)
Establishing a resort in a remote area holds significant potential for tourism development but requires in-depth evaluation of its operational feasibility. This study aims to assess the operational feasibility of establishing a resort in a remote area by considering economic, social, environmental, and infrastructure aspects. The research employs both quantitative and qualitative descriptive analysis methods, with data collected through interviews, field surveys, and literature review. The findings indicate that although there are considerable challenges regarding accessibility and infrastructure, the potential economic benefits from tourism and local development support the operational feasibility of the resort, provided there is policy support and investment in the development of essential infrastructure.